Splenic artery aneurysmal rupture at 24 weeks gestation in a patient with successful in vitro fertilization and embryo transfer after kidney transplantation: a case report - Wenbo Qiao; Xinyue Xiang; Junqing Chu; Yan Lin; Yayu Ren; Feifei Zhou; Chunhua Gao (BMC Nephrology)
Abstract Background Kidney transplantation represents a critical intervention for end-stage renal disease on a global scale. Many women of childbearing age who have received a kidney transplant express a significant desire to conceive. Nevertheless, the occurrence of in vitro fertilization-embryo transfer (IVF-ET) following kidney transplantation remains infrequent. Case presentation A 32-year-old woman, who had undergone kidney transplantation nine years prior and IVF-ET six months ago, presented with abdominal pain. During her hospital stay, she suddenly experienced severe abdominal and chest pain. An abdominal CT angiography revealed a ruptured splenic artery aneurysm with pseudoaneurysm formation, necessitating an emergency exploratory laparotomy and subsequent splenic artery aneurysmectomy. Following the surgery, the patient was transferred to the intensive care unit (ICU) for hemodynamic stabilization, continuous monitoring of fetal heart rate and movement, adjustment of her immunosuppressive regimen, and targeted health education including personalized guidance on immunosuppressive drug management, recognition of pregnancy complications, and fetal monitoring. On the third day in the ICU, with her vital signs stabilized, the patient was transferred to the obstetric ward for further management. In the end, She was successfully maintained until 36 weeks of gestation and delivered a healthy neonate via cesarean section without complications. Conclusion This case report presents the occurrence and management of a splenic artery rupture at 24 weeks of gestation following IVF-ET after kidney transplantation. This case highlights the critical role of multidisciplinary management, individualized fetal monitoring, and optimized immunosuppressive therapy in addressing life-threatening vascular complications in pregnant kidney transplant recipients, providing a valuable reference for similar clinical scenarios. Clinical trial number Not applicable.